2007
DOI: 10.4161/org.3.2.4943
|View full text |Cite
|
Sign up to set email alerts
|

Low-Intensity Ultrasound (LIUS) as an Innovative Tool for Chondrogenesis of Mesenchymal Stem Cells (MSCs)

Abstract: Mesenchymal stem cells (MSCs) have a capacity to differentiate into the chondrogenic lineage and are a valuable allogenic source for cartilage tissue engineering. However, they still have critical limitations of relatively inefficient chondrogenic differentiation in vitro and of dedifferentiation and/or hypertrophic changes at late stages of differentiation. Numerous approaches using biochemical and mechanical factors have been tried but have so far failed to overcome these problems. Recent studies by other gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…(Parvizi et al 1999; Zhang et al 2002; Zhang et al 2003; Ebisawa et al 2004; Schumann et al 2006; Cui et al 2007; Park et al 2007; Korstjens et al 2008; Khanna et al 2009; Gurkan et al 2010; Lai et al 2010; Naito et al 2010). Whether repopulation improves cartilage repair depends on the ability of CPCs to re-establish a functional cartilage matrix in situ , which remains unproven.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Parvizi et al 1999; Zhang et al 2002; Zhang et al 2003; Ebisawa et al 2004; Schumann et al 2006; Cui et al 2007; Park et al 2007; Korstjens et al 2008; Khanna et al 2009; Gurkan et al 2010; Lai et al 2010; Naito et al 2010). Whether repopulation improves cartilage repair depends on the ability of CPCs to re-establish a functional cartilage matrix in situ , which remains unproven.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have shown that LIPUS stimulates cartilage anabolism by enhancing the production of matrix molecules including proteoglycan and collagen (Parvizi et al 1999; Zhang et al 2002; Zhang et al 2003; Korstjens et al 2008; Khanna et al 2009; Naito et al 2010). In addition, LIPUS has been proven to attenuate the progression of cartilage degradation in vivo and has been proposed as a tool to induce mesenchymal stem cells (MSCs) to differentiate into articular chondrocytes (Ebisawa et al 2004; Schumann et al 2006; Cui et al 2007; Park et al 2007; Gurkan et al 2010; Lai et al 2010). However, progress in understanding the mechanism of these benefits has been slow.…”
Section: Introductionmentioning
confidence: 99%
“…Stained images both of whole samples (20Â) and at high magnification (200Â) are presented. Scale bars ¼ 1 mm for 20Â and microenvironment, such as the use of particular scaffolds or some form of mechanical stimulation, might be able to replace the role of TGF-b [46]. The ECM scaffold in this study was synthesized naturally from porcine chondrocytes and could not be optimized in its physicochemical properties, such as exact composition, mechanical strength, pore size and porosity.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical stimulation using low intensity ultrasound, in conjunction with a variety of growth factors, scaffolds and stimulants has also shown to enhance chondrogenesis (Choi et al 2013;Lai et al 2010;Park et al 2007;Lee et al 2007). Such non-invasive and relatively low-cost methods that have been shown to enhance of potential action of MSCs may provide an additional option in the treating physician's armoury.…”
Section: Exogenous Mechanical Stimulationmentioning
confidence: 99%